(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: The author of the review has set himself the goal of presenting a study featuring a revised typology of offenders, which was created in relation to sexual homicide. The authors of the original study took a series of crimes against Human life, the victims of which were women living in a relationship, and reviewed the typological systems that reflected this crime. The result of the systematic review is a femicide typology with a new perspective. Methodology: The authors provide an overview of the typologies of intimate partner homicides and then compare them based on specific criteria system. Findings: In addition to the previous typologies, the analyzes describe a new type, which results in the type of psychopathological offender. Value: The new type of offender widens the spectrum of homicides committed against a sexual/intimate partner, which includes new interpretation possibilities.